2004
DOI: 10.1248/bpb.27.277
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen Peroxide in Bactericidal Action of Catechin

Abstract: Recently green tea, which is the traditional drink of Japan and China, has been recognized as healthful. Catechins, which are polyphenol chemical compounds found in abundance in green tea, possess physiological effects including antioxidative and bactericidal action as well as antitumor activity. Four main catechins are contained within green tea: epicatechin (EC), epicatechin gallate (ECg), epigallocatechin (EGC) and epigallocatechin gallate (EGCg). These catechins display strong antioxidant activity, 1) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
201
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(211 citation statements)
references
References 8 publications
7
201
0
3
Order By: Relevance
“…Some reports have indicated that catechins promote the production of hydrogen peroxide. 40) From the results of our study, catalase prevented GEC-induced growth inhibition of S. mutans, A. naeslundii completely and the antimicrobial activity against S. mutans, A. naeslundii was dependent mainly on hydrogen peroxide. On the other hand, the inhibition zone became smaller in the case of S. aureus and no effect was observed against C. albicans.…”
Section: Discussionmentioning
confidence: 56%
“…Some reports have indicated that catechins promote the production of hydrogen peroxide. 40) From the results of our study, catalase prevented GEC-induced growth inhibition of S. mutans, A. naeslundii completely and the antimicrobial activity against S. mutans, A. naeslundii was dependent mainly on hydrogen peroxide. On the other hand, the inhibition zone became smaller in the case of S. aureus and no effect was observed against C. albicans.…”
Section: Discussionmentioning
confidence: 56%
“…While EGCG can protect cell membranes from lipid peroxidation [19,20], it can also act as a pro-oxidant. At concentrations higher than physiological levels, it produces hydrogen peroxide [2,10,21] that damages DNA and sperm membrane via lipid peroxidation [22,23]. Also, it inhibits sperm chromatin decondensation induced by dithiothreitol in human sperm [24].…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been reported that polyphenolic compounds exert antimicrobial effect via production of H 2 O 2 by auto-oxidation in a liquid medium [70,71], we tried to enhance the antimicrobial activity by means of exposure of polyphenolic compounds to blue light, which enhances the H 2 O 2 production through photo-oxidation of the compounds resulting in hydroxyl radical production via photolysis of the resultant H 2 O 2 ( Fig. 17.2).…”
Section: Other Hydroxyl Radical Generation Systemsmentioning
confidence: 99%